Determinasi Perilaku Pembelian Impulsif Melalui Pendekatan Social, Value, Dan Relaxation Shopping - Ni Kadek Dwi Ervina; Rizka Ageng Pertiwi; Miswanto Miswanto; Baldric Siregar; Frasto Biyanto (Journal of Innovative and Creativity, 2025)
Impulse buying behavior is an increasingly prominent phenomenon in the context of modern retail, along with the development of marketing strategies that emphasize the emotional and psychological aspects of consumers. This study aims to analyze the influence of three dimensions of hedonic motivation in shopping namely social shopping, value shopping, and relaxation shopping on online impulsive buying behavior. This study uses a quantitative approach with a data collection method through a questionnaire distributed to active consumers on the e-commerce platform. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results of the study indicate that social shopping and relaxation shopping have a positive and significant effect on impulsive buying behavior, while value shopping has no significant effect. These findings provide practical implications for e-commerce industry players in designing marketing strategies that can optimize consumer shopping experiences through social and relaxation aspects to encourage positive impulsive buying behavior.